TEACHING STRATEGY OF AL-ISLAM TEACHER ON INCREASING STUDENTâS MORALITY IN 9 GRADE OF SMP MUHAMADIYAH 15 SURABAYA - Fathullah, Ahmad (Studia Religia, 2018)
AbstractThis study aimed to determine the role of teacher to studentâs moralityeducation, the strategy of Al - Islam teacher to improve student morality, thesupporting factors and inhibitors in building studentâs morality of 9 gradestudent in SMP Muhammadiyah 15 Surabaya. This study used descriptivequalitative method. The research data were collected by using observation,interview and documentation method, then analyzed by using inductiveapproach and validity test. The results indicated that: activities of moralformation that teachers do i.e. night prayer, tahfidz Qurâan, and dzuhur prayingin congregation. Teaching strategies of PAI Teacher used inquiry strategies,approached to student by using a variety of methods such as lecturing method,habituation method, and counseling method. The supporting factors: (a)family factors or parent who has very active role to participate in fosteringstudentâs morality, (b) environment or community around the school, (c) theenvironment around studentâs residence has been thick with religious thing, (d)schoolâs rules to prevent studentâs delinquency. Inhibiting Factors are (a) therewas no enough time to foster much morality on student. (b) Lack of schoolâsprovision. (c) Different studentâs attitude and behavior. (d) Uncontrollablestudent association. (e) Lack of studentsâ awareness to attend activities requiredby the school. (f) Inadequate supporting facilities and infrastructures. (g) Thewidespread of information today.Â Keywords: Role, Strategy, Moral Education